Perilaku Mencit (Mus musculus) terhadap Feses Ular Kobra Jawa (Naja sputatrix): The Behavior of Mice (Mus musculus) towards Feces Stimulant from Javanese Spitting Cobra (Naja sputatrix) - Kartika Marta Djakaria; Nurhardiyanti Munawaroh, Anggi; Mardilah; Quraisy Zakky; Ruhama Maya Sari; Berry Juliandi (Jurnal Sumberdaya Hayati, 2020)
This research aimed to confirm the predator avoidance behavior of mice from snake droppings as a stimulant. Snake droppings are obtained from snakes fed with mice that come from the same strain as the mice being tested for response. Snake droppings were diluted into three different concentrations (25%, 50%, and 75%). The results showed that male individuals tend to avoid the odor stimuli than the female, it’s shown by the higher avoidance duration in males than the females. The results also indicate that innate behavior takes role in the avoidance response since the mice have never been exposed to any presence of predator.